2018
DOI: 10.1001/jamaoncol.2018.2100
|View full text |Cite
|
Sign up to set email alerts
|

Preferred Clinician Communication About Stopping Cancer Screening Among Older US Adults

Abstract: 2. Thompson LD. Ninety-four cases of encapsulated follicular variant of papillary thyroid carcinoma: a name change to noninvasive follicular thyroid neoplasm with papillary-like nuclear features would help prevent overtreatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 7 publications
0
29
0
Order By: Relevance
“…A recent study of adults aged 65 years and older reported that, although older adults were amenable to using age and health status within the context of discussing screening cessation, there were concerns with discussions overly focused on life expectancy . Another study found that patients prefer clinicians to frame the decision to stop screening in terms of prioritizing other health issues . As in all interactions between providers and patients, an informed, shared decision with clear communication of the risks and benefits of cancer screening or treatment should be the centerpiece of clinical care.…”
Section: Selected Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study of adults aged 65 years and older reported that, although older adults were amenable to using age and health status within the context of discussing screening cessation, there were concerns with discussions overly focused on life expectancy . Another study found that patients prefer clinicians to frame the decision to stop screening in terms of prioritizing other health issues . As in all interactions between providers and patients, an informed, shared decision with clear communication of the risks and benefits of cancer screening or treatment should be the centerpiece of clinical care.…”
Section: Selected Findingsmentioning
confidence: 99%
“…61 Another study found that patients prefer clinicians to frame the decision to stop screening in terms of prioritizing other health issues. 62 As in all interactions between providers and patients, an informed, shared decision with clear communication of the risks and benefits of cancer screening or treatment should be the centerpiece of clinical care. Although most guidelines generally recommend against cancer screening in those with less than a 10-year life expectancy, differences across organizations can complicate decisions for patients and their providers.…”
Section: Cancer Screeningmentioning
confidence: 99%
“…[12][13][14] Because best practices for discussing cancer screening cessation are largely undefined, we explored, in our prior work, older adults' preferred communication strategies for clinicians to discuss stopping cancer screening. 15 We found that older adults most preferred their clinicians to describe stopping cancer screening in relation to "focusing on other health priorities" while discussing discomfort or inconvenience of the screening test, life expectancy, or not bring up a discussion were viewed more negatively. 15 The main limitation of this prior work was that it relied on an existing online survey panel.…”
Section: Introductionmentioning
confidence: 87%
“…15 We found that older adults most preferred their clinicians to describe stopping cancer screening in relation to "focusing on other health priorities" while discussing discomfort or inconvenience of the screening test, life expectancy, or not bring up a discussion were viewed more negatively. 15 The main limitation of this prior work was that it relied on an existing online survey panel. Although the panel is nationally representative in demographic composition, the panelists tend to have high health literacy which may be an important determinant of the way patients would like to receive information about stopping cancer screening.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation